Fast and solvent‐free microwave‐assisted synthesis of thermoresponsive oligo(glycidyl ether)s. Issue 21 (21st September 2018) - Stöbener, Daniel D.; Donath, Dorian; Weinhart, Marie
ABSTRACT: Low‐molecular weight linear poly(glycidyl ether)s are typically synthesized via the "classical, " oxy‐anionic ring‐opening polymerization (ROP) of glycidyl ether monomers at elevated temperatures. To reduce reaction times, a fast process was developed to synthesize oligo(glycidyl ether)s (OGEs) in bulk at a gram‐scale utilizing microwave heating. Well‐defined thermoresponsive copolymers comprising glycidyl methyl ether and ethyl glycidyl ether with molecular weights of up to 3 kDa were synthesized via microwave‐assisted ROP with reaction times of approximately 10 min. The fast reaction kinetics were attributed to the rapid and uniform heating and high temperatures reached during the reaction. Consequently, no significant microwave‐specific acceleration of the oxy‐anionic ROP was observed. The temperature‐triggered phase transition of the OGEs in aqueous solution revealed cloud point temperatures that are highly dependent on the OGE molecular weight, concentration, and comonomer composition, which extends previously reported data. Furthermore, oligo(glycidyl ether) acrylates (OGEAs) with reactive, functional end groups were directly accessible via in situ quenching of the anionic, microwave‐assisted ROP with acrylic acid chloride. The obtained thermoresponsive OGEA macromonomers represent a promising material for the functionalization of surfaces via radical grafting methods to obtain functional, thermoresponsive coatings with potential application in cell culture. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 2496–2504 Abstract : The gram‐scale, solvent‐free synthesis of thermoresponsive oligo(glycidyl ether)s was developed using microwave heating. By comparing the reaction kinetics with the conventional oxy‐anionic ring‐opening polymerization, fast reaction rates could be solely attributed to thermal effects. Well‐defined oligomers with tunable phase transition temperatures dependent on concentration, comonomer ratio, and molecular weight were synthesized with molecular weights up to 3 kDa. Furthermore, reactive acrylate macromonomers for radical grafting‐through polymerization reactions were obtained by in situ quenching.